DEMAND ANALYSIS FOR STRATEGIC FOOD IN INDONESIA DURING ECONOMIC CRISIS AND ITS IMPLICATION ON FOOD CONSUMPTION AMONG HOUSEHOLDS WITH CHILDREN UNDER TWO YEARS - Resti Mauludyani, Anna Vipta; Fahmida, Umi; Santika, Otte (GIZI INDONESIA, 2013)
The objective of  the  study  is  to analyze demand elasticity for strategic foods  during economic crisis and its  implication  on  food and  nutrient consumption among  household  in Indonesia.  This ecological study was  conducted  to  14,767  households  owned  children  less  than  two  years  included  in  National Socioeconomic  Survey  2007.  Analysis  was  conducted  by  using  econometric  model  of  Double-Log Regression in SAS program. Result of analysis showed that the own-price elasticities were all found to be negative  as  expected,  meaning  that  increased  price  of  strategic  food  tended  to  reduce  its  demand.  Inconclusion, the effect of  food crisis was visible to most of the strategic foods   which their demand tendedto be highly affected by price changes. This effect was mostly seen in rural and low income household swhich  had  limited  income  to  purchase  food.  Improved  income  tended  to  increase  demand  of  strategic foods. Demand on protein sources were highly affected by income changes.Keywords: demand analysis, strategic food, food consumption, nutrient intake.